Secondary Failure of Oral Therapy in Patients With Type 2 Diabetes - How To Overcome It? - Marković, Aleksandra; Dojčinović, Tamara; Risović, Ivona; Grujičić, Milorad; Malinović Pančić, Jelena (Scripta Medica, 2025)
Background/Aim: Secondary failure of oral therapy occurs after a long period of successful use of oral antidiabetic drugs. The exact mechanism of its occurrence is not known. Recent data suggest heterogeneity of this phenomenon, analogous that of type 2 diabetes pathogenesis. Research objective was to assess glucoregulation and insulin secretory function before, three months after the use of insulin therapy and three months after the exclusion and re-introduction of oral antidiabetic therapy.Methods: Forty-nine patients with unsatisfactory glycaemic control were selected and insulin therapy in four daily doses (basal-bolus regimen) was subsequently initiated. Glycaemic regulation and beta cell function (C-peptide and insulinemia) were monitored at three time points: before starting insulin therapy, three months after initiating insulin and three months after discontinuing insulin and resuming the previously used oral antidiabetics.Results: After the introduction of insulin therapy, there was a significant improvement in glycaemic regulation parameters (p < 0.001). Improvements in beta-cell function and reductions in insulin resistance were confirmed during the period after insulin therapy (p < 0.001). However, a certain deterioration in these parameters was observed following the discontinuation of insulin therapy. Additionally, there was a slight decrease in C-peptide and an increase in insulinemia, though these changes were not statistically significant.Conclusion: Application of intensified insulin therapy for three months leads to improvement of glucoregulation and partial recovery of the secretory function of the endocrine pancreas. The reintroduction of oral antidiabetic therapy led to a slight worsening of the observed parameters, although this change was not statistically significant.